Screening of dephytinization reaction of chlorophyll pigments with citrus acetone powder by UPLC–DAD–MS. Issue 1 (14th December 2022) - Li, Yunchang; Agarry, Israel Emiezi; Ding, Desheng; Zalán, Zsolt; Huang, Pimiao; Cai, Tian; Chen, Kewei
Abstract : Abstract: The preparation of dephytylated chlorophyll standards is inefficient and the process is complicated, which hinders chlorophyll determination and related bioactive property investigation. In this paper, chlorophyll derivatives from four phytylated chlorophylls (chlorophyll a, chlorophyll b, pheophytin a, and pheophytin b ) before and after the enzymatic reaction were qualitatively and quantitatively characterized by UPLC–DAD–MS. A simple index was proposed to characterize chlorophyll pigments from their oxidized counterparts by the λ max of the typical peak of chlorophyll derivatives in UV–visible spectrum and their signal intensity ratios. The optimal reaction conditions for the enzymatic reaction of four chlorophyll pigments were optimized, and kinetic models were fitted. The results showed that the optimal temperatures for the enzymatic reactions of chlorophyll a, chlorophyll b, pheophytin a, and pheophytin b were 30, 30, 60, and 60°C, respectively, and their optimal reaction time was 2, 3, 1, and 3 h, respectively. Kinetic models were fitted under optimal reaction conditions to study the K m and V m values of the enzymatic reactions. Practical Application: Dephytylated chlorophylls, such as chlorophyllide and pheophorbide, are frequently determined in food industry and are always required to be prepared in lab with acetone powder from plant tissue. Moreover, chlorophyll pigments are easy to undergo oxidations, which make the characterization of dephytylated chlorophyll pigments more complicated and difficult. In this paper, four types of phytylated chlorophylls were investigated respectively about the dephytinization process with the citrus acetone powder, and the reaction mixture was analyzed with UPLC–DAD–MS, which can provide an important reference for relevant chlorophyll determination studies and the development of chlorophyll identification protocols.